2017
DOI: 10.1111/bjet.12600
|View full text |Cite
|
Sign up to set email alerts
|

What motivates enrolment in programming MOOCs?

Abstract: Learners who enrol in massive open online courses (MOOCs) have different backgrounds and tend to have different motivations than learners in traditional courses. Based on value-expectancy theory, an instrument was developed to measure motivation for enrolling in a programming MOOC. A study with 1229 adult participants in Estonian-language programming course "About Programming" was conducted to validate the instrument. Results of confirmatory factor analysis validated the 7-factor scale named factors influencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…Therefore, the authors measured and reported these five variables in the current study. Motivation was measured by combining and consolidating key motivation items from previous validated MOOC studies (Luik et al, 2017; Milligan & Littlejohn, 2017; Watted & Barak, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the authors measured and reported these five variables in the current study. Motivation was measured by combining and consolidating key motivation items from previous validated MOOC studies (Luik et al, 2017; Milligan & Littlejohn, 2017; Watted & Barak, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…SPSS version 25.0 was used for statistical data analysis. First, composite scores of individual items from the FIEM scale were calculated based on seven factors (Luik et al, 2019). The second step focused on building motivation clusters from composite score results of the FIEM scale.…”
Section: Discussionmentioning
confidence: 99%
“…Studying motivation in MOOCs, it is important to understand the value and worth of the MOOC for the participant (Macdonald & Ahern, 2015). A wide range of motivations for using MOOCs has been described (Kizilcec & Schneider, 2015;Luik et al, 2019;Milligan & Littlejohn, 2017;Zheng et al, 2015). It has been found that the learners who enroll in MOOCs tend to have different motivations than learners in traditional courses (Watted & Barak, 2018).…”
Section: Motivation In Moocsmentioning
confidence: 99%
See 1 more Smart Citation
“…in order to participate and complete the course. Moreover, they tend to have different motivations than audiences in traditional courses [35]. In the context of ILMx MOOCs, we made our email communication both informative and beneficial (e.g., providing useful websites; recommended readings and activating the new Dynamic Pacing-weekly content highlight feature on edX etc.)…”
Section: Learning By Doing: Moocs In Land Managementmentioning
confidence: 99%